Une étude génétique des traductions allemandes de Senghor au prisme des archives berlinoises - Giuseppe Sofo (Continents manuscrits)
This article is devoted to a genetic analysis of German translations of Léopold Sédar Senghor’s work, based on documents held in two archives kept at Humboldt University in Berlin: the archives of Janheinz Jahn, translator responsible for the publication of hundreds of works of African and West Indian literature into German, and the archives of Erica de Bary (1907-2007), writer and translator who was Senghor’s first translator into German. On the basis of the epistolary exchanges of Jahn with Senghor, de Bary and a third translator, Friedhelm Kemp (1914-2011), de Bary’s working drafts and the published versions of Jahn’s translations, as well as a hitherto unknown and uncatalogued version that we discovered during our research, we will analyse the genetic evolution of Senghor’s texts in German, as well as the dynamics of collaboration between Jahn and the other translators, whose work has remained entirely unknown until now.